Design, synthesis and properties of a reactive chromophoric/fluorometric probe for hydrogen peroxide detection. (21st April 2017) - Zhang, Yu; Jiao, Zinuo; Xu, Wei; Fu, Yanyan; Zhu, Defeng; Xu, Jiaqiang; He, Qingguo; Cao, Huimin; Cheng, Jiangong
Abstract : A succinct chromophoric/fluorometric probe, AVPM, for sensitive and selective H2 O2 detection. Abstract : As the most important starting material and degradation product of peroxide explosives, H2 O2 is considered as a signature compound for peroxide-based explosives. A new probe, (2-(2, 6-bis(( E )-2-(10-(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)anthracen-9-yl)vinyl)-4 H -pyran-4-ylidene)malononitrile) (AVPM), for both chromophoric/fluorometric detection of H2 O2 was designed and synthesized. AVPM emitted a long wavelength emission from its intramolecular charge transfer (ICT) and hence its absorption was expanded to the visible region. The response rate and sensitivity of AVPM for H2 O2 detection were tremendously improved (91% of the fluorescence was quenched within 2 min for H2 O2 ) by adding triethylamine (TEA) into the probe solution. And the solution color changed from yellow to blue. A detection limit down to 17.58 nM is remarkably achieved. These features lead to a new chromophoric/fluorometric probe for H2 O2 detection and make it an ideal candidate for chemical detection and analysis in public safety and environmental monitoring.